2017
DOI: 10.2147/ott.s124012
|View full text |Cite
|
Sign up to set email alerts
|

Tbx2 confers poor prognosis in glioblastoma and promotes temozolomide resistance with change of mitochondrial dynamics

Abstract: Tbx2 is a cancer-related protein that was found to be overexpressed in several human malignancies. The present study aims to investigate the clinical significance and biological role of Tbx2 in human astrocytoma. We examined its protein expression in 102 cases of astrocytoma tissues using immunohistochemical staining. Negative Tbx2 staining was observed in normal astrocytes, and positive nuclear staining was found in 41 out of 102 astrocytoma specimens. The rate of Tbx2 overexpression in pylocytic astrocytoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…DEG analysis also included increased expression of SLC6A1, SLC6A11, and GABBR2 in VWM, which encode major transmembrane γ-aminobutyric acid (GABA) transporters GAT-1, GAT-3, and GABAb receptor subunit 2, respectively. 38 In contrast to the protective effect of TBX2, our VWM human WM astrocytes also showed a decreased expression of MT2A, an antioxidative, anti-inflammatory, and antiapoptotic metallothionein secreted by astrocytes that is well known for its neuroprotective properties. This may further lead to astrocytic glutamate release, thereby potentiating inhibitory synaptic transmission, and to astrocytic ATP/adenosine-mediated heterosynaptic suppression affecting excitatory transmission.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…DEG analysis also included increased expression of SLC6A1, SLC6A11, and GABBR2 in VWM, which encode major transmembrane γ-aminobutyric acid (GABA) transporters GAT-1, GAT-3, and GABAb receptor subunit 2, respectively. 38 In contrast to the protective effect of TBX2, our VWM human WM astrocytes also showed a decreased expression of MT2A, an antioxidative, anti-inflammatory, and antiapoptotic metallothionein secreted by astrocytes that is well known for its neuroprotective properties. This may further lead to astrocytic glutamate release, thereby potentiating inhibitory synaptic transmission, and to astrocytic ATP/adenosine-mediated heterosynaptic suppression affecting excitatory transmission.…”
Section: Discussionmentioning
confidence: 64%
“…In astrocytoma cell lines, TBX2 has been shown to promote proliferation, to inhibit cleaved caspase 3-mediated apoptosis by stimulating mitochondrial fission, and to increase mitochondrial DNA content. 38 In contrast to the protective effect of TBX2, our VWM human WM astrocytes also showed a decreased expression of MT2A, an antioxidative, anti-inflammatory, and antiapoptotic metallothionein secreted by astrocytes that is well known for its neuroprotective properties. 39 Mitochondrial mechanisms involved in VWM pathophysiology corroborate recent findings in primary astrocytes of Eif2b5 R132H/R132H mice indicating that an impaired oxidative phosphorylation in these cells is compensated by increased mitochondrial content and glycolysis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We found that most of those probes identified in 7 cancers are located in non-island regions. Moreover, some genes of those CpG sites located have been reported to be associated with the prognosis of various cancers (such as SHANK2 [31], LTBP1 [32], GRIA4 [33], OSR2 [33], PHLDB2 [34], TBX2 [35][36][37] and GPR37 [38]). Currently, no qualified independent dataset is available for systematically estimating the reproducibility and validity of the probe-based prognostic classifier, thus a further verification of this prognostic model would be necessary in the future.…”
Section: Prognostic Model Successfully Divides Patients Into High-rismentioning
confidence: 99%
“…As noted above, both pathological and clinical studies have shown that higher DRP1 expression is correlated with worse prognosis in patients concurrently treated with TMZ and irradiation [43,44].…”
Section: Silencing Of Drp1 Expression In Gbm Cells Decreases Cell Gromentioning
confidence: 74%